Examining the Communication Effects of Health Campaigns: A Case Study Using Find Thirty Every Day® in Western Australia - Leavy, Justine; Bauman, A.; Rosenberg, M.; Bull, F. (Sage Publications, Inc, 2014)
Community-wide health communication campaigns have been used for over 30 years to increase awareness of the benefits of physical activity. The relationship between raising campaign awareness influencing physical activity behavior directly or through intermediate variables has not been fully explored. The aims of this study were to examine the relationship between campaign awareness and four socio-cognitive variables on changes in physical activity levels among a cohort of adults exposed to a physical activity campaign. Find Thirty every day® was a population-wide, serial mass media campaign delivered in Western Australia. There was a significant association between campaign awareness and higher outcome expectations. The likelihood of higher outcome expectations and higher decisional balance was significantly greater in people who maintained campaign awareness compared with people who had no/relapsed campaign awareness. Those with higher compared with lower outcome expectation, self-efficacy, social support, and decisional balance were more likely to remain sufficiently active. A significant proportion of people who remained insufficiently active were not aware of the campaign. Finally, we found an association between the four individual socio-cognitive variables and levels of change in physical activity that appeared to be independent. The article adds to a small but growing body of literature that reinforces the importance of target audience refinement in physical activity mass media campaigns.